Integration of Entrepreneurship Education in the Pondok Pesantren Curriculum: A Case Study at Hidayatul Mubtadi-ien in Indramayu - Oman Faturahman; Sulaiman, Sulaiman; Marliani, Lina; Muhammadun, Muhammadun; Nasikhin, Moch Mahdiyan; Karim, Abdul (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2023)
Purpose – This research aims to explore the integration of entrepreneurship education within the curriculum of the Pondok Pesantren Hidayatul Mubtadi-ien in Indramayu, Indonesia, and its impact on the character development and self-reliance of the students (santri). Design/methods/approach – This research was conducted through in-depth interviews, participatory observation, and document analysis using a qualitative case study method. A thematic analysis approach was applied to identify key themes from the data collected over a six-month research period. Findings – The results indicate that Pondok Pesantren Hidayatul Mubtadi-ien has successfully integrated entrepreneurship education with Islamic values. This is reflected in the curriculum, daily activities, and projects involving the students. Government involvement in project funding demonstrates an essential synergy between educational institutions and the government. The practical approach to entrepreneurship education in the pesantren has proven effective, creating a dynamic and interactive learning environment. Research implications – These findings provide theoretical and practical contributions to developing entrepreneurship education management in Pondok Pesantren and education in Indonesia more broadly. This research opens up opportunities for further studies on the implementation of entrepreneurship education in other educational institutions and expands the scope of research on the role of entrepreneurship education in the character development and self-reliance of students. The limitations of this research, such as the specific context of the pesantren and available resources, offer opportunities for broader and more in-depth research in the future.